Ejercicios de Williams y su influencia en adultos mayores con lumbalgia que acuden al área de rehabilitación Hospital General Martín Icaza en el periodo junio - septiembre 2024. - Ube Coronel, Daniela Elizabeth (2024)
Low back pain is one of the most common health problems today and can occur at any age. Activities such as lifting heavy weights and poor postural hygiene are some of its main causes. In this sense, the older adult population, due to the natural aging of the body, is more prone to wear and tear of the vertebral discs, joints and other spinal structures, which causes difficulty in carrying out some of their daily living activities, such as wash, cook, sew work. According to the World Health Organization (WHO), low back pain is the main cause of disability in the world, limiting normal work and recreational activities. This project is carried out with the purpose of analyzing the impact that the different Williams exercises have on older adults with low back pain who attend the rehabilitation area of the Martín Icaza General Hospital. These exercises reduce chronic pain in the lower back, strengthen the abdominal muscles and the muscles that provide stability to the spine. On the other hand, due to the lack of knowledge on the part of the older adult population about this topic, this project also seeks to provide information about low back pain and the exercises that relieve its symptoms. The methodologies used in this project are descriptive, observational, explanatory and deductive; as quantitative, documentary and field modality; Finally, the type of research is basic and correlational. To obtain the results, surveys, EVA tests, goniometric measurements and the Oswestry survey were used, through which it was found that 57% of the study population was female, most of them between 65 and 69 years of age, 33% stated that they performed Williams exercises often and 50% considered that they had adequate duration, even so, 43% mentioned that the Williams exercises had a moderate difficulty and 20% considered them very difficult. 60% managed to feel a considerable decrease in pain while 50% reported feeling general relief, this relief lasting between 3 to 6 hours after performing the Williams exercises. Finally, with regard to daily activities, 70% mentioned having difficulty performing them and 43% reported improvements in this aspect after applying the exercises.